Comparative Study of Sexual Function Between Post-Hypospadias Repair and Post-Circumcision Patients - Zen, Ong Xin; Mohd Shah, Mohd Shahrulsalam; Wan Sulaiman, Wan Azman; Mohamed Daud, Mohamed Ashraf (Malaysian Journal of Medical Sciences, 2026)
Background: Hypospadias is the most common congenital anomalies of the male genitalia. Literature on sexual function outcome post-hypospadias repair is scarce, especially in the Southeast Asian population. This study compares the sexual function between hypospadiacs post-repair and healthy circumcised adult males.Methods: This study was conducted in Hospital Pakar Universiti Sains Malaysia (HPUSM). Convenience sampling of patients who underwent hypospadias repair from 1995 to 2005 was done. Healthy circumcised males were recruited as controls. This questionnaire-based study utilised an adaptation of the Global Sexual Functioning (GSF) questionnaire, Sexual Satisfaction Score (SSS) questionnaire, and Penile Perception Score (PPS).Results: 49 questionnaires were sent to eligible subjects after screening, while 80 questionnaires were sent to suitable controls. 26 subjects and 75 controls responded. The control group was older [34.43 (±5.789) vs. 28.92 (±7.255) years]. The control group reported better scores in sexual function, sexual satisfaction, and penile cosmesis. The GSF scores showed a low negative correlation with SSS (r = –0.384) when both groups were analysed together. A similar pattern was seen in the control but not the hypospadias group. The correlation between SSS and PPS differed between control and subject, indicating a discordant pattern across groups.Conclusion: This study revealed that post-hypospadias repair patients demonstrated poorer sexual function compared to circumcised controls. SSS is reliable in assessing sexual satisfaction in hypospadiacs. There is a low negative correlation between GSF score and SSS. Better penile cosmesis assessed using PPS translates to better sexual satisfaction in circumcised controls, but the result is discordant in hypospadiacs.